2010
DOI: 10.1021/pr9010266
|View full text |Cite
|
Sign up to set email alerts
|

N-Glycomic Changes in Human Breast Carcinoma MCF-7 and T-Lymphoblastoid Cells After Treatment with Herceptin and Herceptin/Lipoplex

Abstract: The humanized monoclonal antibody IgG1 in combination with chemotherapy has been demonstrated to enhance survival benefit in cancer treatment. Despite positive outcomes, some cancer cells develop multidrug resistance. Numerous mechanisms in cancers can be involved in the process of treatment therapy and most of them are not still well understood. To address how the carbohydrate moieties of cells are affected during treatment, the glycan profiles from the two most common cancer cell lines s human breast MCF-7 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 54 publications
6
34
0
Order By: Relevance
“…1B for glycan structures). These glycans were also detected in Trastuzumab using a different methodology [57]. Although glycan standards can be utilized to confirm structure in capillary electrophoresis, the cost and limited commercial availability make it impractical to use glycan standards to probe structural characteristics.…”
Section: Phospholipid Separations and Glycan Analysis Of Trastuzumabmentioning
confidence: 99%
“…1B for glycan structures). These glycans were also detected in Trastuzumab using a different methodology [57]. Although glycan standards can be utilized to confirm structure in capillary electrophoresis, the cost and limited commercial availability make it impractical to use glycan standards to probe structural characteristics.…”
Section: Phospholipid Separations and Glycan Analysis Of Trastuzumabmentioning
confidence: 99%
“…Kudo et al (13) showed that N-glycan alterations were associated with drug resistance in human hepatocellular carcinoma. Lattova et al (14) reported that N-glycomic changes in human breast carcinoma MCF-7 and T-lymphoblastoid cells occurred after treatment with herceptin and herceptin/Lipoplex. Our results also showed that glycomic alterations were associated with MDR in human leukemia (15).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the same batch of Herceptin used for treatment in our study underwent a thorough analysis of glycans, as reported previously (19). Furthermore, a detailed analysis of glycopeptides obtained from the antibody is presented here along with the investigation of glycosylated peptides isolated from treated samples, to validate the profiles observed.…”
Section: Resultsmentioning
confidence: 83%
“…Both types of these experiments showed also differences at the proteome level. The monitoring of N-glycans in cancer cells before and after exposure to the antibody showed significant alterations in glycosylation (19). Dominant high-mannose glycans (Man 5-9 GlcNAc 2 ) accompanied by less abundant of fucosylated tri-and tetrantennary higher sialylated glycans were found in both original cancer cells and after treatment these structures were replaced by complex biantennary fucosylated oligosaccharides of the same compositions as found in IgG1.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation